Electrochemical energy conversion and storage systems for future sustainability : technological advancements - Samantara, Aneeya Kumar; Ratha, Satyajit (Burlington, ON, Canada ; Palm Bay, Florida, USA : Apple Academic Press, 2021)
"This new volume discusses new and well-known electrochemical energy harvesting, conversion, and storage techniques. It provides significant insight into the current progress being made in this field and suggests plausible solutions to the future energy crisis along with approaches to mitigate environmental degradation caused by energy generation, production, and storage. Topics in Electrochemical Energy Conversion and Storage Systems for Future Sustainability: Technological Advancements address photoelectrochemical catalysis by ZnO, hydrogen oxidation reaction for fuel cell application, and miniaturized energy storage devices in the form of micro-supercapacitors. The volume looks at the underlying mechanisms and acquired first-hand information on how to overcome some of the critical bottlenecks to achieve long-term and reliable energy solutions. The detailed synthesis processes that have been tried and tested over time through rigorous attempts of many researchers can help in selecting the most effective and economical ways to achieve maximum output and efficiency, without going through time-consuming and complex steps. The theoretical analyses and computational results corroborate the experimental findings for better and reliable energy solutions. The chapters provide a clear understanding of the background and working principles of several well-known energy harvesting and storage technologies. In addition, the new concepts discussed, such as microsupercapacitors, CO oxidation, and CO2 reduction, will provide opportunities for further research and development in the relevant field. Key features: considers the role of nanostructured materials and their conjugates for sustainable energy, reviews practical applications of the prototypes developed from nanostructured materials, addresses the shortcomings of traditional battery technologies, shows the advantage of electrochemical capacitors and fuel cell, emphasizes the important role of various parameters on the charge storage performance of the electrochemical capacitors."--
Metal Chalcogenide-Based Electrochemical Capacitors / Satyajit Ratha and Aneeya Kumar Samantara -- Photoelectrochemical Reduction of CO2 and Electrochemical Oxidation of CO / Surjendu Bhattacharyya and Biswajit Mishra -- Hybrid Polymer Nanocomposites for Energy Storage/Conversion Devices: From Synthesis to Applications / Anil Arya and A.L. Sharma -- Process, Design, and Technological Integration of Flexible Microsupercapacitors / Syed Mukulika Dinara -- Catalytic Activities of Carbon-Based Nanostructures for Electrochemical CO2 Reduction: A Density Functional Approach / Mihir Ranjan Sahoo -- Catalyst for Hydrogen Oxidation Reaction and Its Application to Energy Storage / Avijit Biswal and Avinna Mishra -- Theoretical and Computational Investigations of Li-Ion Battery Materials and Electrolytes / Anoop Kumar Kushwaha -- Effect of Morphology and Doping on the Photoelectrochemical Performance of Zinc Oxide / Akash Sharma, Pooja Sahoo, Alfa Sharma, and Saswat Mohapatra -- Methanol and Formic Acid Oxidation: Selective Fuel Cell Processes / Tapan Kumar Behera, Pramod Kumar Satapathy, and Priyabrat Mohapatra.
OCLC-licensed vendor bibliographic record.
Keywords: Electric power production from chemical action; Electrochemistry; Fuel cells; Energy storage; SCIENCE / General; SCIENCE / Energy; TECHNOLOGY / Engineering / Chemical & Biochemical